2020
DOI: 10.3390/foods9081013
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Atmospheric Dielectric Barrier Discharge Plasma against Escherichia coli and Bacillus cereus on Dried Laver (Porphyra tenera)

Abstract: This study investigated the effects of atmospheric dielectric barrier discharge (DBD) plasma (1.1 kV, 43 kHz, 5–30 min, N2: 1.5 L/m) on the reduction of Escherichia coli and Bacillus cereus on dried laver. The reductions of E. coli and B. cereus by 5, 10, 20, and 30 min of DBD plasma were 0.56 and 0.24, 0.61 and 0.66, 0.76 and 1.24, and 1.02 and 1.38 log CFU/g, respectively. The D-value of E. coli and B. cereus was predicted as 29.80 and 20.53 min, respectively, using the Weibull model for E. coli (R2 = 0.95) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…The linear model described by first-order kinetics is widely used to determine the D -value for microorganisms, which can accurately predict the linear microbial inactivation curve [ 16 , 22 , 23 ]. In addition, the Weibull model has been successfully applied to better fit nonlinear microbial inactivation curves [ 24 , 25 , 26 , 27 , 28 , 29 ]. A better temperature and heating uniformity control for each kinetic inactivation can make the fitting equation more accurate.…”
Section: Introductionmentioning
confidence: 99%
“…The linear model described by first-order kinetics is widely used to determine the D -value for microorganisms, which can accurately predict the linear microbial inactivation curve [ 16 , 22 , 23 ]. In addition, the Weibull model has been successfully applied to better fit nonlinear microbial inactivation curves [ 24 , 25 , 26 , 27 , 28 , 29 ]. A better temperature and heating uniformity control for each kinetic inactivation can make the fitting equation more accurate.…”
Section: Introductionmentioning
confidence: 99%
“…The first‐order kinetics model is commonly used to determine the decimal reduction time in thermal and nonthermal processes. In this study, to obtain D‐values, a semilogarithmic graph using log N0 (CFU/g) versus plasma application times was used (Kim et al., 2020 ). The results showed that D‐values decreased with increasing plasma power and exposure time.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of NaOCl for HNoV GII.4 in Manila clams using a first‐order kinetics model is as follows:logNN0goodbreak=k2.303twhere N 0 is the initial microbial population (log copy/μl), N is the microbial population after NaOCl treatment (log copy/μl), t is the treatment concentration (mg/L), and k is the reduction rate constant (Choi et al, 2022; Kim, Jeon, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…where N 0 is the initial microbial population (log copy/μl), N is the microbial population after NaOCl treatment (log copy/μl), t is the treatment concentration (mg/L), and k is the reduction rate constant (Choi et al, 2022;Kim, Jeon, et al, 2020).…”
Section: Modeling Microbial Reductionmentioning
confidence: 99%